Effects of Salinit:y on the Germination and Growth of Radicle and Plumule of Bajra (Pennisetum Typhoides) Varieties - Saxena, M B.L; Kolarkar, A S (Annals of Arid Zone, 2016)
Varieties Babapuri, RSK and hybrid BJ 104 of pearl millet were tested for their tolerance to six levels of water salinity at germination. Per cent germination, radicle length and plumule length were studied. Varaties Babapuri and BJ 104 withstood high salinity better than RSK on account of their longer radicles and plumules and these characters are suggested as criterion in selection for salinity tolerance.